Recommendations for the treatment of hypertension in the elderly and very elderly – a scotoma within international guidelines (Swiss Medical Weekly, 2012)
The recommendations of international scientific societies for the treatment of hypertension in the geriatric population are different. Lack of outcome trials, non-standardised terminology as well as differing levels of evidence contribute to the inconsistencies in the guidelines. This review article compares six international guidelines (ESH-ESC 2007/2009, SHG 2009, DHL 2008, CHEP 2010, NICE 2011 and JNC7 2003) as well as the consensus document of the ACCF/AHA 2011 in terms of their recommendations of drug classes, target blood pressure values and the use of combination therapy. Generally, antihypertensive therapy appears to be clinically beneficial in geriatric patients. Target blood pressure values of